The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1164/rccm.200905-0685oc
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Corticosteroid Response in Chronic Obstructive Pulmonary Disease Using Exhaled Nitric Oxide

Abstract: Fe(NO) is a weak predictor of short-term response to oral corticosteroid in COPD, its usefulness being limited to predicting increase in FEV(1). Clinical trial registered with www.anzctr.org.au (ACTRN12605000683639).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 32 publications
3
50
2
Order By: Relevance
“…The results of the study showed that exhaled nitric oxide is a weak predictor in patients with COPD and that a normal or low test result could help clinicians decide to avoid prescriptions of oral corticosteroid treatment that may be unnecessary. This result was in agreement with other previous study [38]. These observations help us to expect that those patients with COPD would have greater systemic inflammatory marker activation and those with asthma would have more local inflammatory marker activation.…”
Section: Discussionsupporting
confidence: 93%
“…The results of the study showed that exhaled nitric oxide is a weak predictor in patients with COPD and that a normal or low test result could help clinicians decide to avoid prescriptions of oral corticosteroid treatment that may be unnecessary. This result was in agreement with other previous study [38]. These observations help us to expect that those patients with COPD would have greater systemic inflammatory marker activation and those with asthma would have more local inflammatory marker activation.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast to asthma, FeNO is less useful in predicting the short-term ICS response in stable COPD, although it predicts treatment response in acute exacerbations of COPD. Dummer et al [48] showed that whilst a raised FeNO is a weak predictor of short-term response to oral steroids in patients with stable, moderately severe COPD, a normal FeNO result has clinical utility in predicting the absence of a response. It was pointed out that in the context of treating COPD, in which at best only 20% of patients will demonstrate steroid responsiveness, this information would help the clinician avoid prescribing unnecessary ICS treatment [48].…”
Section: Cluster Analysis In Chronic Obstructive Pulmonary Diseasementioning
confidence: 99%
“…Exhaled nitric oxide (FE NO ) is a surrogate of large airway inflammation and has an established role in asthma [6]. The use of FE NO as a biomarker in COPD, however, is questionable [7]. Cigarette smoking is known to suppress FENO levels in COPD patients [8], and evidence of elevation of FE NO in COPD patients is inconsistent [9,10].…”
Section: Introductionmentioning
confidence: 99%